IMPLEMENTASI KOMUNIKASI INTERPERSONAL KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU DI SMK MUHAMMADIYAH 2 BANDAR LAMPUNG - Nurul Aisyah; Abdurrahman Abdurrahman; Ilhami Ilhami (Jurnal Manajemen Pendidikan, 2026)
This study aims to analyze the implementation of the principal's interpersonal communication through the dimensions of openness, empathy, and support and how these three dimensions significantly contribute to improving teacher performance at SMK Muhammadiyah 2 Bandar Lampung. The urgency of this research is motivated by the limited number of qualitative studies that deeply explore the practice of interpersonal communication of principals in the context of religious-based private vocational high schools in Indonesia. The method used is a descriptive qualitative approach with data collection techniques in the form of observation, interviews, and documentation. The results show that the principal's interpersonal communication plays a crucial role in building a healthy, open, and mutually supportive working relationship between the principal and teachers. The openness dimension is realized through regular discussion forums and teacher involvement in decision-making. The empathy dimension is reflected in the principal's attitude of actively listening and understanding the teacher's condition. Meanwhile, the support dimension is present in the form of motivation, supervision, and encouragement of professional development. The findings of this study provide a conceptual contribution to the development of educational management studies while offering a practical perspective for principals in optimizing interpersonal communication as an effective leadership strategy.